Implementation of the Governor's Policy Regarding Free Education in Improving The Quality of Education of State Vocational Schools in Banten Province - Suyudi, Imam; Sudadio, Sudadio; Suherman, Suherman (Mudir : Jurnal Manajemen Pendidikan, 2023)
Education is the process of educators communicating science, technology and art to students, as a tool to change ways of thinking from traditional to modern. This is supported by the government's commitment to making policies based on laws containing professionalism and progress in education from the aspect of facilities to matters of financing. The purpose of this study is to provide an overview and analyze the effectiveness, results, and observations of the supporting or inhibiting factors of the implementation of the governor's policy on free education. The research was conducted in the work area of the Banten Province Education and Culture Office, focusing on Vocational High Schools in Banten Province from July 2021 to July 2023. This research used a qualitative approach. This type of research used a multi-site study. The direct data source is the natural setting to analyze the overall data, then the quality of education at the State Vocational High Schools in Banten Province is the focus of this research, the formal findings and the focus of the substantive research findings. This research illustrates that the implementation of the free education policy is a program, its success depends on good and straightforward organizational or management actors to be used as a forum for creating skilled and quality generations.